2022
DOI: 10.2147/copd.s348714
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Among Older Individuals with and without COPD: A Cohort Study of Prevalence and Association with Adverse Outcomes

Abstract: Rationale Frailty prevalence estimates among individuals with COPD have varied widely, and few studies have investigated relationships between frailty and adverse outcomes in a COPD population. Objective(s) Describe frailty prevalence among individuals with and without COPD and examine associations between frailty and mortality and other adverse outcomes in the next two years. Methods This was an observational cohort study using Health and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The characteristics of the included studies are presented in Table 1 . These studies were published between 2011 and 2022, and 24 of them were cross-sectional studies [ 6 , 7 , 19 , 21 41 ], 8 of which were longitudinal studies [ 17 , 42 48 ] and the remaining 6 cohort studies [ 12 , 49 53 ]. In total, 19,362 participants from 13 countries were included in the analysis, with the main geographic locations in the United States (eight studies) [ 28 , 38 , 40 , 44 46 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are presented in Table 1 . These studies were published between 2011 and 2022, and 24 of them were cross-sectional studies [ 6 , 7 , 19 , 21 41 ], 8 of which were longitudinal studies [ 17 , 42 48 ] and the remaining 6 cohort studies [ 12 , 49 53 ]. In total, 19,362 participants from 13 countries were included in the analysis, with the main geographic locations in the United States (eight studies) [ 28 , 38 , 40 , 44 46 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, hormonal factors such as low blood androgens and estrogens may be involved in the development or progression of frailty 40 and increased risk of cognitive impairment in older men 41 . Furthermore, the prevalence of frailty is higher in people with chronic diseases such as chronic obstructive pulmonary disease (COPD) than those without COPD 42 . A meta‐analysis study showed that in people with Chronic obstructive pulmonary disease (COPD) or chronic heart failure, prone to contracted pneumonia, the prevalence of mild cognitive impairment (MCI) was higher than in the general population 43 .…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, the prevalence of frailty is higher in people with chronic diseases such as chronic obstructive pulmonary disease (COPD) than those without COPD. 42 A metaanalysis study showed that in people with Chronic obstructive pulmonary disease (COPD) or chronic heart failure, prone to contracted pneumonia, the prevalence of mild cognitive impairment (MCI) was higher than in the general population. 43 They assumed that hypoxemia, inflammation, and vascular disease might be involved in the development of MCI in those patients.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…COPD also has a systemic effect, and its comorbidities are common; between 51% to 90% of people with COPD are estimated to have more than one comorbid condition, and up to 97% in those with GOLD stage 4 COPD [ 2 , 3 , 4 , 5 ]. Furthermore, frailty is common, with 23% of people with COPD being classified as frail and 56% as prefrail [ 6 , 7 , 8 ]. Falling is a prominent feature of the frailty syndrome, and therefore, it is unsurprising that people with COPD are four times more likely to fall than healthy adults without COPD.…”
Section: Introductionmentioning
confidence: 99%